PENGARUH KODE ETIK PROFESI TERHADAP KINERJA APARAT PENEGAK HUKUM DI INDONESIA - Ma'adul Yaqien Makkarateng (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2022)
AbstractThe professional code of ethics is a norm set and accepted by a group of professions that direct or instruct their members how to do and at the same time ensure the quality of the profession ahead of the community. Violation of the professional code of ethics is a deviation from the norms established and accepted by a group of professions, which directs or instructs its members how to do and at the same time guarantees the quality of the profession in the front of the public. Man is the most perfect creature of God and even man is equipped with an attitude about which knowledge and behavior are good and which are evil from the laws of nature, which can be dug through reason, within the framework of the theory of nature law, wise people will live well. This attitude is the happiest that God the Creator wants.